Identification and characterization of a heme exporter from the MRP family in Drosophila melanogaster. - Wang, Z.; Zeng, P.; Zhou, B. (BMC Biology, 2022)
The heme group constitutes a major functional form of iron, which plays vital roles in various biological processes including oxygen transport and mitochondrial respiration. Heme is an essential nutrient, but its pro-oxidant nature may have toxic cellular effects if present at high levels, and its synthesis is therefore tightly regulated. Deficiency and excess of heme both lead to pathological processes; however, our current understanding of metazoan heme transport is largely limited to work in mammals and the worm Caenorhabditis elegans, while functional analyses of heme transport in the genetically amenable Drosophila melanogaster and other arthropods have not been explored. We implemented a functional screening in Schneider 2 (S2) cells to identify putative heme transporters of D. melanogaster. A few multidrug resistance-associated protein (MRP) members were found to be induced by hemin and/or involved in heme export. Between the two plasma membrane-resident heme exporters CG4562 and CG7627, the former is responsible for heme transit across the intestinal epithelium. CG4562 knockdown resulted in heme accumulation in the intestine and lethality that could be alleviated by heme synthesis inhibition, human MRP5 (hMRP5) expression, heme oxygenase (HO) expression, or zinc supplement. CG4562 is mainly expressed in the gastric caeca and the anterior part of the midgut, suggesting this is the major site of heme absorption. It thus appears that CG4562 is the functional counterpart of mammalian MRP5. Mutation analyses in the transmembrane and nucleotide binding domains of CG4562 characterized some potential binding sites and conservative ATP binding pockets for the heme transport process. Furthermore, some homologs in Aedes aegypti, including that of CG4562, have also been characterized as heme exporters. Together, our findings suggest a conserved heme homeostasis mechanism within insects, and between insects and mammals. We propose the fly model may be a good complement to the existing platforms of heme studies.